2004
DOI: 10.2460/javma.2004.224.1821
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic findings in horses with subtle radiographic evidence of osteochondral lesions of the medial femoral condyle: 15 cases (1995–2002)

Abstract: Results suggest that horses with hind limb lameness and subtle radiographic lesions of the medial femoral condyle are likely to have arthroscopically apparent cartilage lesions and subchondral bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…As expected, no lesions were seen in the menisci confirming the findings of previous studies regarding the high clinical relevance of any abnormality detected in the meniscus [17,20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, no lesions were seen in the menisci confirming the findings of previous studies regarding the high clinical relevance of any abnormality detected in the meniscus [17,20].…”
Section: Discussionsupporting
confidence: 91%
“…Subchondral bone cysts are most common in the medial femoral condyle, at the point of load bearing in the joint, but have also been described in the lateral femoral condyle [16]. Ultrasonography is superior to radiography for diagnosis of small subchondral cysts 16 and these lesions can be clinically silent [17,18]. While the presence of subchondral cyst-like lesions are most commonly described in Thoroughbreds, they can seen in many different breeds [19].…”
Section: Discussionmentioning
confidence: 99%
“…More severe erosions were present for horses in the long-term cohort, compared with the short-term cohort, suggesting that the osteoarthritis was progressive; however, the widespread loss of the superficial cartilage layer for horses in the short-term cohort indicates that these joint surfaces are likely to degenerate further, with little chance for recovery. 49,50 By the time stifle joint osteoarthritis creates detectable clinical signs, relatively advanced cartilage lesions are found that are likely to progress quickly, leading to a guarded prognosis in affected horses. 69 Damage to the articular cartilage of the weightbearing surface of the MFC has been described in horses and is believed to be the cumulative effect of repeated trauma.…”
Section: Discussionmentioning
confidence: 99%
“…44 The pathogenesis of subchondral cystic lesions in the MFC of horses may be related to the creation of osteochondral defects of an appropriate size and shape. [48][49][50] Although osteochondrosis may cause this damage in young horses, 49 the cumulative effect of repeated trauma is more likely the cause in mature animals. 44,47 However, the nature and magnitude of the insult and whether it is a single event or requires repeated injury remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation